The inglorious years the collapse of the industrial order and the rise of digital society - Cohen, Daniel, 1953- (Princeton University Press, 2021)
"Suspicion and distrust in the workplace, people protesting all over the world, the younger generation imprisoned in a sort of perpetual, virtual present.... These are the consequences of the collapse of industrial society and the consequent disappearance of jobs and lowering of wages for the vast majority. But is the new digital society any better? Or is it simply transforming us all into sequences of information that can be manipulated by software from anywhere in the globe? Has yesterday's production line been replaced by the dictatorship of algorithms? Are social networks a way of formatting minds? In an astounding return to the past, the questions of the ancient world are resurfacing at the heart of the new. Times are changing, but are they moving in the right direction? This book explores the ways in which we have been let down by the new tide of technology that promised to solve many of the conundrums that humanity found itself in during the twentieth century. Cohen argues that our new interconnectivity, which once heralded the decline of inequality and a people-led recalibration of the ethics of capitalism, has not fulfilled its promise. The revolutionary excitement of 1968, a time when people imagined a future of technological liberation and unfettered prosperity, was never realised. Instead the rise of populism is but one manifestation of the profound disappointment felt by many with a post-industrial society which has left them feeling marginalised and deprived of the possibility of a better life. What does the new digital society hold in store for us and how can we regain control of our lives?"--